Logistics Analysis Of Corn (Zea mays L) Production On Spacing And Weed Control In Tanjung Agung Palik Vilagge, North Bengkulu - Munhedi Munhedi; Rika Dwi Yulihartika; Yossie Yumiati (University of Prof. Dr. Hazairin, SH, 2022)
Corn is a food plant that contains carbohydrates which are commonly found in agricultural fields, especially corn cultivation. Therefore, it is possible that corn plants will always be developed considering the large market demand or processed into flour and snacks, even used in the livestock sector as an ingredient for animal feed. therefore it is not surprising that corn crops will continue to be improved.The research was conducted in the village of Tanjung Agung Palik ,research purposes to analyze the logistics of corn production on spacing and weed control. The results showed that farmers can use a spacing of 75 x 20 cm. Meanwhile, to suppress weed growth so that corn plants get sunlight and nutrients that are suitable for the needs of corn plants to be able to carry out photosynthesis. The method in this research is the Binary Logistics Regression model. Binary Logistics Regression in this study was used to see the effect of the independent variable on the dependent variable. The results showed that the variable spacing and weed control only affected 1.9%. The results of the production of chemical respondents were 72 people with a percentage of 40%, while the results of natural production were 18 people with a percentage of 20%.